Bibliometric Analysis: Trends In Japanese Linguistics Studies (2004-2024) - Adnyani, Kadek Eva Krishna; Gede Satya, Hermawan; Yeni (Denpasar Institute, 2025)
The study of Japanese linguistics has gained growing attention in recent decades as global interest in Japanese language and culture continues to expand. This research maps trends and emerging topics in Japanese linguistic studies from 2004 to 2024 using bibliometric analysis. Data were collected from Google Scholar through Publish or Perish and analyzed with VOSviewer, resulting in 29 relevant terms classified into five clusters. Network visualization revealed strong interconnections across research areas, with central terms such as Japanese linguistics, applied linguistics, and discourse frequently bridging multiple clusters, confirming the increasing relevance of discourse analysis in language studies. Overlay visualization highlighted the temporal evolution of research, showing that since 2020, topics such as cognitive linguistics and intercultural communication have gained prominence, reflecting a broader transition from structural approaches toward cognitive and socio-cultural perspectives. Density visualization further demonstrated that established areas like Japanese linguistics and applied linguistics are highly saturated, while emerging fields remain underexplored and present opportunities for innovation. This study provides valuable insights into evolving research directions and encourages further exploration of cognitive and intercultural perspectives in Japanese linguistics